Multiple Linear Regression (MLR) and Principal Component Regression (PCR) for ozone (O3) concentrations prediction - Mohd Napi N.N.L.; Noor Mohamed M.S.; Abdullah S.; Mansor A.A.; Ahmed A.N.; Ismail M. (IOP Publishing Ltd, 2023)
Air quality; Economics; Environmental technology; Forecasting; Linear regression; Nitrogen oxides; Ozone; Wind; Air quality levels; Correlation coefficient; Influencing parameters; Multicollinearity; Multiple linear regressions; Principal component regression; Principle component analysis; Principle component regression; Predictive analytics